In vitro influence on fibrinolysis parameters of aqueous extracts of mushrooms growing on woody plants - N. M. Faustova; D. N. Vedernikov; V. V. Bakanov; E. N. Pavlova; E. N. Vlasova; Yu. A. Skorik (Разработка и регистрация лекарственных средств, 2024)
Introduction. Various compounds of mushroom extracts are of interest as a source of new active pharmaceutical substances with antithrombotic activity.Aim. The aim of the work is to determine the potential antithrombotic activity in vitro of aqueous extracts of xylotrophic mushrooms: Lentinula edodes, Pholiota squarrosa, Flammulina velutipes (Curtis) Signer, Kuehneromyces mutabilis, Armillaria cepistipes, Armillaria borealis, Hypholoma capnoides, Lentinellus cochleatus, Léccinum aurantíacum, Pleurotus ostreatus.Materials and methods. The study of fibrinolytic activity of water extracts of mushrooms in vitro was carried out. The effect of test objects on plasminogen activation, on the activity of enzyms of the fibrinolysis system α2-antiplasmin, on the time of euglobulin clot lysis and on the concentration of fibrinogen was evaluated. For the analysis we used reagent kits of SPD «RENAM» and LLC Company «Тechnology-Standard» (Russia).Results and discussion. Pronounced antithrombotic activity is demonstrated by an aqueous extract of L. edodes and fractions of aqueous extract. Extracts of L. edodes affect all studied parameters of fibrinolysis to varying degrees. Caps and stems of P. squarrosa, K. mutabilis, and F. velutipes aqueous extracts and fractions of aqueous extracts also demonstrate antithrombotic (fibrinolytic) activity in vitro, having a statistically significant effect on various parameters of fibrinolysis. A less pronounced effect on fibrinolysis parameters in comparison with the above samples is observed when using an aqueous extract of L. cochleatus marked. A. cepistipes, A. borealis, H. capnoides, L. aurantiacum, P. ostreatus fruiting bodies aqueous extracts do not affect the studied parameters of fibrinolysis and the concentration of fibrinogen.Conclusion. The data obtained make it possible to recommend extracts from L. edodes, F. velutipes, P. squarrosa and K. mutabilis for further study, for example, in order to develop functional food products for cardiovascular diseases or to create antithrombotic drugs.